The Effect of the Minimum Wage on Prices - Sara Lemos (Institute for the Study of Labor (IZA), 2004)
It is well established in the international literature that minimum wage increases compress the wages distribution. Firms respond to these higher labour costs by reducing employment, reducing profits, or raising prices. While there are hundreds of studies on the employment effect of the minimum wage, there is less than a handful studies on its profit effects, and only a couple of dozen studies on its price effects. Not only is the literature scanty on the minimum wage price effects, but also it lacks a survey on that. This survey represents an important contribution to the literature because it summarizes and critically compares over twenty price effect studies, providing a benchmark in the literature. This survey further contributes to the literature by offering an input to the recent debate over the direction of employment effects of the minimum wage. With employment and profits not significantly affected, higher prices is an obvious response to a minimum wage increase. Moreover, this survey also contributes to the literature by extending the current understanding on the minimum wage as a policy against inequality and poverty. If the minimum wage does not cause disemployment but causes inflation, it might hurt rather than aid the poor, who disproportionately suffer from inflation.
Keywords: J38; 330; minimum wage; wage effect; employment effect; price effect informal sector; cost shock; Mindestlohn; Arbeitskosten; Preisniveau; Welt